Principles of Environmental Sciences - Boersema, Jan J.; Reijnders, Lucas (Springer Netherlands : Imprint: Springer, 2009)
Principles of Environmental Sciences provides a comprehensive picture of the principles, concepts and methods that are applicable to problems originating from the interaction between the living and non-living environment and mankind. Both the analysis of such problems and the way solutions to environmental problems may work in specific societal contexts are addressed. Disciplinary approaches are discussed but there is a focus on multi- and interdisciplinary methods. A large number of practical examples and case studies are presented. There is special emphasis on modelling and integrated assessment. This book is different because it stresses the societal, cultural and historical dimensions of environmental problems. The main objective is to improve the ability to analyse and conceptualise environmental problems in context and to make readers aware of the value and scope of different methods. The authors contributing to Principles of Environmental Sciences come from several countries and a wide variety of scientific backgrounds in the fields of natural and social sciences, and the humanities. This book will be ideal as a course text for students, and will also be of interest to researchers and consultants in the environmental sciences.